COGNITIVE RECONSTRUCTION TO REDUCE ANXIETY IN GRADE VI ELEMENTARY SCHOOLS - Inggit Kartika Sari; Erny Hidayati (UIN Sunan Kalijaga, 2020)
Abstract. This study aims to determine the effect of group therapy with cognitive reconstruction techniques to reduce anxiety in grade VI elementary school students. The subjects in this study were grade VI students, male or female sex, and experiencing anxiety. Data collection methods in this study are through observation, interviews, Discussion Group Forums (FGD), and pre-test and post-test using the Hamilton Anxiety Rating Scale (HARS). The data analysis technique used a non-parametric test with the Wilcoxon test. The results showed that there was a decrease in anxiety both qualitatively and quantitatively. Qualitative results indicate that participants can think positively, bolder, more confident, and try to do something happily, while the quantitative results show the value of Z = -2,371 with a significance of p = 0.018 (p <0. 05) on the HARS anxiety scale which means there was a significant difference between the anxiety experienced by participants before and after attending group therapy. Based on the results of the research that has been done it can be concluded that group therapy with cognitive reconstruction techniques can reduce anxiety levels in grade VI elementary school students.Keywords: anxiety, cognitive reconstruction, class VI students, group therapy